2012
DOI: 10.1017/s1368980011003570
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the WHO Child Growth Standards in rural Honduras

Abstract: Objective: The present study analysed the impact of using the 2006 WHO Child Growth Standards ('the WHO standards') compared with the 1977 National Center for Health Statistics (NCHS) international growth reference ('the NCHS reference') on the calculated prevalence of chronic malnutrition in children aged 6?0-59?9 months. Design: Anthropometric data were collected as part of a cross-sectional study exploring the association between household environments and nutritional status of children. Z-scores were compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Subjects completed questionnaires on lifestyle, bowel habits, and dietary intake and submitted them at the hospital visit. Anthropometric measurements, including height, weight, waist circumference, midarm circumference, hip circumference, thigh circumference, and blood pressure, were performed by professionally trained personnel [ 14 , 15 ]. Body composition analysis including skeletal muscle mass and total body fat content was measured using the inBody 770 analyzer (Biospace Co. Ltd., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects completed questionnaires on lifestyle, bowel habits, and dietary intake and submitted them at the hospital visit. Anthropometric measurements, including height, weight, waist circumference, midarm circumference, hip circumference, thigh circumference, and blood pressure, were performed by professionally trained personnel [ 14 , 15 ]. Body composition analysis including skeletal muscle mass and total body fat content was measured using the inBody 770 analyzer (Biospace Co. Ltd., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies in the literature used now obsolete child growth standards ( 6 , 20 , 21 ) or used a variety of incomparable cut-off points to define malnutrition ( 1 , 12 , 22 , 23 ) . The currently recommended WHO child growth standards ( 24 ) give higher estimates for both stunting and overweight compared with the earlier standards of the US National Center for Health Statistics ( 25 ) and the US Centers for Disease Control and Prevention ( 26 ) , and this poses serious problems concerning comparison of studies using the various standards. To enable valid comparisons across years, studies are needed that apply the new WHO growth standards to data that pre-date the new standards, as well as newer data.…”
mentioning
confidence: 99%
“…Only one study in the American Region presented children with lower growth outcomes in comparison to WHO growth standards (Martin et al, 2019). The evaluation in Honduras showed children who presented with lower height-for-age means but higher weight-forage and weight for height z scores in comparison to WHO growth standards (Nichols et al, 2012). Only one study in the Americas presented a curve that approximated the WHO growth standards (da Silva Vieira et al, 2015).…”
Section: Comparison With Local Growth References And/or Local Populationmentioning
confidence: 99%
“…Research conducted in Brazil showed a growth trajectory similar to WHO growth standards for exclusively breastfed children compared to the NCHS 1977 growth reference (da Silva Vieira et al, 2015). A study done in Honduras showed that WHO standards were able to detect more children with stunting, overweight, and obesity but identified fewer underweight children compared to NCHS 1977 growth references (Nichols et al, 2012).…”
Section: Comparison Between International Growth Referencesmentioning
confidence: 99%